Adaptation in adversity: innovative approaches to food security amidst COVID-19 in a remote First Nations community in Canada - Fatima Ahmed; Robert J. Moriarity; Nicholas D. Spence; Gisele Kataquapit; Celine Sutherland; Nadia A. Charania; Leonard J. S. Tsuji; Eric N. Liberda (BMC Public Health)
Abstract The COVID-19 pandemic exacerbated food insecurity issues in geographically isolated communities, including Fort Albany First Nation (FAFN). This research examines FAFN’s adaptive strategies to improve food security, highlighting community resilience and leadership. Data were gathered through semi-structured interviews with 20 community members who were involved in the pandemic response, either as members of the pandemic committee or as managers of community programs. Thematic analysis revealed significant adaptation of existing programs and the establishment of new initiatives to address food security during the pandemic. Initiatives, such as the community garden and the Fort Albany Farmers Market were food security programs that existed prior to the pandemic, and despite labor shortages during the pandemic, logistical hurdles were addressed to maintain operations and enhance food distribution efficiency. New emergency food initiatives, backed by government support and community efforts, successfully delivered food to vulnerable households. Traditional subsistence activities, such as hunting and fishing, were essential for providing sustenance and strengthening community resilience. These adaptive strategies highlight the critical role of local leadership, community participation and ingenuity, and the utilization of Indigenous knowledge in overcoming food security challenges during crises. This paper underscores the need to support Indigenous food sovereignty and build resilient local food systems tailored to the unique needs of First Nations communities. The experiences of FAFN during the COVID-19 pandemic provide invaluable insights into the resilience and innovation required to improve food security in remote and vulnerable populations, emphasizing the need for sustained investment and policy support in these communities.